Biological Studies on Sonneratia Caseolaris Obtained From The Selangor River, Peninsular Malaysia - Loo, Khai Kin (2005)
Sonneratia caseolaris is a display tree for fireflies in Kuala Selangor. Fireflies has become a tourist attraction to this area and contribute to the economy of the people related to the industry. S. caseolaris trees are found in abundance in certain sections along the Selangor river which are influenced by both freshwater from the upperstream and seawater during high tide. Analysis of the important elements in the plants showed that the nitrogen content in the sediment, branches and leaves were 1.50 + 0.05 mglg, 5.62 + 0.14 mglg and 22.79 k 1.08 mglg, respectively. The soil nitrogen content was decreasing from the upper stream to the seaward sites. The nitrogen content of the leaves of S. caseolaris grown in the upper stream was higher than those of trees grown in the seaward sites. The phosphorus content in the sediment, branches and leaves were 1.02 + 0.03 mglg, 0.258 r 0.01 mglg and 0.58 r 0.03 mglg, respectively. The phosphorus content in the leaves of trees at the upper stream was higher than those of the seaward sites. The potassium content in sediment, branches and leaves were 9.27 * 0.31 mglg, 14.69 r 0.58 mglg and 31.85 + 1.10 mglg, respectively. The distribution of potassium was more at the seaward sites and to a lesser extent at the upper stream. However, the potassium concentration in leaves grown at the upper stream was higher than the seaward sites. These results suggest the influence of water movement in distributing nutrients to the S. caseolaris habitat along the Selangor river system. S. caseolaris produced large numbers of fruits that may contain over a thousand seeds per fruit of which around 90% are viable. Seed germination seems to be the only way of propagation of this plant. Laboratory studies showed that high salinity inhibited the germination seeds of S. caseolaris. The inhibition was proportional with the salinity. Only about 2% of the seeds germinated in seawater. The present study also showed that salinity affected the stem height of the seedlings. The stem height was reduced at 13.0 and 26.0%0 salinity. The xylem, pith cells, parenchyma cells of the cortex and air spaces of the stem seedlings were also smaller than the stem of the seedlings treated at lower salinity (0 - 6.5%0). The shape of leaves grown under high salinity (13.0 and 26.0%0) were more rounded and the leaves of the seedlings grown under low salinity (0, 3.3 and 6.5%0) were longer. The leaf mesophyll and the parenchyma cells of the seedlings exposed to high salinity (13.0 and 26.0%0) were also smaller than the seedlings exposed to low salinity (0 - 6.5%0). The increase of salinity had resulted in the increase of the vapor pressure deficit, which on the other hand, reduced transpiration and stomata conductance. This study also showed that suspended solids and inundation levels may influence the growth of the seedlings. The stem height, total and average leaf area, length and width of the leaf and root fresh weight and internal structure of the seedlings were varied with the levels of suspended solids and the inundation level.